Weekly carfilzomib plus cyclophosphamide and dexamethasone in the treatment of relapsed/refractory multiple myeloma: Final results from the MCRN‐003/MYX.1 single arm phase II trial. Issue 5 (12th April 2021) - Venner, Christopher P.; LeBlanc, Richard; Sandhu, Irwindeep; White, Darrell; Belch, Andrew R.; Reece, Donna E.; Chen, Christine; Dolan, Sean; Lalancette, Marc; Louzada, Martha; Kew, Andrea; McCurdy, Arleigh; et al.
Abstract: The MCRN‐003/CCTGMYX.1 is a single arm phase II trial of weekly carfilzomib, cyclophosphamide and dexamethasone (wKCd), exploring a convenient immunomodulator (IMiD)‐free regimen in relapsed myeloma. Weekly carfilzomib (20/70 mg/m 2 ), dexamethasone 40 mg and cyclophosphamide 300 mg/m 2 was delivered over 28‐day cycles. The primary endpoint was overall response after four cycles. Secondary endpoints included toxicity, response depth, PFS and OS. Exploratory endpoints included the impact of cytogenetics, prior therapy exposure and serum free light chain (sFLC) escape; 76 patients were accrued. The ORR was 85% (68% ≥very good partial response [VGPR] and 29% ≥complete response [CR]). The median OS and PFS were 27 and 17 months respectively. High‐risk cytogenetics conferred a worse ORR (75% vs. 97%, p = .013) and median OS (18 months vs. NR, p = .002) with a trend toward a worse median PFS (14 vs. 22 months, p = .06). Prior proteasome inhibitor (PI) or lenalidomide did not influence OS or PFS. The sFLC was noted in 15% of patients with a median PFS of 17 months when included as a progression event. The most common ≥ grade 3 non‐hematologic adverse events were infectious (40%), vascular (17%) and cardiac (15%). The wKCD is a safe and effective regimen in relapse, especially for patients ineligible for lenalidomide‐based therapies.